Reduce pain scale in post-surgery percutaneus coronary intervention (PCI) patients with Benson relaxation in the cathlab room Al Adan Hospital - Mukhamad Irkham (South East Asia Nursing Research, 2022)
Postoperative (post-op) percutaneous coronary intervention (PCI) patients had complaints of pain including chest pain and pain in the area where the surgery was punctured. One of the actions that can be taken to reduce pain can be overcome with non-pharmacological therapy in the form of Benson relaxation techniques. This case study aims to describe nursing care for postoperative PCI patients who are given nursing actions using Benson relaxation techniques to reduce pain. The design of this case study uses a descriptive approach to the nursing care process with two respondents, by providing the Benson relaxation technique which is carried out for 2 x 15 minutes. Pain scale measurements were carried out before and after doing Benson relaxation. The pain scale measurement tool uses the Numeric Rating Scale (NRS). The results of this case study show that apart from being given pharmacological measures, the Benson relaxation technique can help patients reduce pain in post-op PCI patients, whereas in patients I and II after being given relaxation measures there is a change in the pain scale from a moderate pain scale to a mild pain scale. Giving Benson relaxation is effective in helping to reduce the scale of post-PCI surgery pain.